Evidence of the evolved nature of the B[e] star MWC 137 - Muratore, M. F. (2015)
The evolutionary phase of B[e] stars is difficult to establish due to the un certainties in their fundamental parameters. For instance, possible classications for the Galactic B[e] starMWC 137 include pre- main-sequence and post-main-sequence phases, with a large range in luminosity. Our goal is to clarify the evolutionary stage of this peculiar object, and to study the CO molecular component of its circumstellar medium. To this purpose, we modeled the CO molecular bands using high-resolution K-band spectra. We nd that MWC137 is surrounded by a detached cool (T = 1900100 K) and dense (N = (31)1021 cm2) ring of CO gas orbiting the star with a rotational velocity, projected to the line of sight, of 84 2 kms1. We also nd that the molec- ular gas is enriched in the isotope 13C, excluding the classication of the star as a Herbig Be. The observed isotopic abundance ratio (12C=13C = 25 2) derived from our modeling is compatible with a proto-PN, main-sequence or supergiant evolutionary phase. However, based on some observable characteristics of MWC137, we propose that the supergiant scenario seems to be the most plausible. Hence, we suggest that MWC137 could be in an extremely short-lived phase, evolving from a B[e] supergiant to a blue supergiant with a bipolar ring nebula.